STATUS HUKUM PEMEGANG HAK MILIK ATAS SATUAN RUMAH SUSUN DENGAN SERTIFIKASI HAK GUNA BANGUNAN YANG TERBIT DIATAS HAK PENGELOLAAN SETELAH BERAKHIRNYA HAK GUNA BANGUNAN - Desi Kurnia Lestari (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
Government Regulation Number 24 of 1997 on Land Registration Article 1 (1) describes what is meant by the land registry is a series of activities undertaken by the government on an ongoing basis, continuous and regular covering the collection, management, accounting, and presentation as well as the maintenance of physical data and juridical data in the form of maps and lists, the plots and units of flats, including the provision of letters and proof of its right to the land areas of existing rights and property rights on apartment units that encumber. Based on the description in background the above, then that becomes a problem in this thesis is how the agreement between the Right of Ownership on Unit Flats with certificate of Right to buildings are rising on the Right Stewardship and How Legal Status Holder Properties is and role of Officer Deed Land (PPAT) in the manufacturing process deed Development and Stewardship agreements. Type of thesis research is a normative legal research.Results of the research agreement between the Upper Unit Properties Flats with certificate of Right to buildings that rise over ownership rights Stewardship is a shared ownership flats and can not be owned individually, used and enjoyed together. Legal Status Holder Properties Top Unit Flats with certificate of Right to buildings that rise over management rights after the end of Right to buildings is after flats are built, then the Operator Construction make descriptions and Deed of Separation on each apartment unit and then by a second letter, Certificate issuance organizers pleaded Development Property Rights on Unit Flats on each apartment units in the building to the local Land Office. Role of Land Deed Officer (PPAT) must consider the rights to be obtained landlord so that no one harmed both consumers / occupant or PT. Pinang Jaya as a provider of Non-Residential Housing Unit. Keywords: certificates, property, apartment units.